Reinforcing Digital Citizenship Literacy through Exploration and Reflection in Civic Education - Anggraheni, Dini; Makarim, Sayoto; Anandha, Anandha; Yogatama, Adiprana (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of digital technology is reshaping how young people learn, communicate, and participate in civic life. Guided by Ribble’s digital citizenship framework and Choi’s multidimensional model, this study examines the level of digital citizenship literacy among Indonesian high school students. It proposes a practical reinforcement model for civic education, using a quantitative, descriptive design and a cross-sectional survey. Data were collected from 40 eleventh-grade students using a validated 19-item questionnaire covering four dimensions: digital awareness, digital ethics, digital social responsibility, and digital civic participation. Results show a high overall literacy level (86.94%), with students demonstrating strong social responsibility and civic participation but lower critical awareness of digital information. Significant correlations among dimensions indicate that ethical awareness helps shape responsible civic engagement. Based on these findings, a Two-Phase Reinforcement Model was developed, emphasizing value exploration and critical reflection. This model offers a relevant approach for strengthening civic education in Indonesia’s transition toward a human-centered digital.